EPA-lactone derivative, 5,6-diHETE lactone, improves pulmonary arterial hypertension in a monocrotaline-induced model - Dhananjayan, Karthik; Ertracht, Offir; Atar, Shaul; Livoff, Alejandro; Shehadeh, Mona; Szuchman-Sapir, Andrea (Frontiers in Pharmacology, 2025)
BackgroundPulmonary arterial hypertension (PAH) is a progressive pulmonary arteriopathy characterized by vascular remodeling and subsequent increases in pulmonary vascular resistance, which further develops into right ventricular failure and death. Currently, PAH management targets pulmonary vasoconstriction, though there is an unmet medical need to develop therapeutics focusing on pulmonary vascular remodeling. Recently, we reported that 5,6-diHETE lactone (EPA-L, a stable metabolite of the EPA fatty acid) elicits vasodilation and blood-pressure-lowering effect in 5/6 nephrectomy hypertensive rats and vasodilation in human arterioles by an endothelial-dependent mechanism.AimWe aimed to investigate the effect of EPA-L in a monocrotaline (MCT)-induced rat model of PAH.MethodsSprague-Dawley Rats were divided into four groups; 3 received MCT (60 mg/kg, s. c.), and the control group was treated with saline. After 3 weeks, MCT rats were treated with saline, 0.3 or 3.0 mg/kg EPA-L, for five consecutive days. Finally, all animals were sacrificed upon functional, hematological, and histological evaluations.ResultsEPA-L administration (i.v.) significantly reduced mean pulmonary arterial pressure (p < 0.05), echocardiographic pulmonary artery time-to-peak (p < 0.05), arterioles intimal-media thickness (p < 0.05) compared to the MCT group. Blood chemistry resulted in a significant reduction in hypoxic indices following the EPA-L administration, but it did not reduce the macrophage infiltration to the lungs and indicators of systemic inflammation, such as neutrophil count and % lymphocyte.ConclusionIn addition to the dilation properties, EPA-L attenuates MCT-induced pulmonary hypertension by improving hemodynamic parameters, and vascular modification. Therefore, EPA-L may act as a promising candidate for treating PAH.